Do split-side rails present an increased risk to patient safety?. Issue 2 (1st April 2005) - Hignett, S; Griffiths, P
Abstract : Background: Concerns have been raised about the safety of split-side bed rails for patients in the UK. Objectives: To investigate whether split-side rails were more likely to be associated with entrapment and injury of patients than other bed rail types. To establish whether there was a difference in the site of injury caused by different bed rail types and whether the outcome of the injury (death versus survival) varied by bedrail type. Methods: A search of the USA Food and Drug Administration MAUDE database was carried out. The reports were screened using rigorous inclusion/exclusion criteria and then coded for rail type, incident outcome, and area of body involved. Results: Split-side rail incidents only accounted for 5% of the reports and were more likely to involve the chest or pelvis. Although the biggest overall risk by rail type cannot be determined from these data, the severity of the outcome changed with the equipment type. Incidents involving half rails were more likely to be associated with head, neck, or face entrapments and were also more likely than other bed rail types to result in death. Discussion: Split-side rail entrapments were not a common occurrence. However, our findings suggest that bed rails are associated with some level of risk of entrapment that potentially could result in death. Healthcare providers should therefore ensure that they follow the guidelines for risk assessment and rail use from the MHRA and other professional bodies so that the cultural norm in the UK continues to be "opt in", where no bed rails are used unless indicated by a documented clinical assessment.